2005
DOI: 10.1007/s10725-005-1435-3
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species, calcium and serine/threonine phosphatase are required for copper-induced MAP kinase geneOsMAPK2, expression in rice

Abstract: Regulation of the MAP kinase gene (OsMAPK2) expression in rice under metal, copper, stress conditions was investigated. OsMAPK2 transcript accumulation was enhanced by copper and H 2 O 2 in rice root-tip cells. To investigate how the OsMAPK2 gene is regulated in response to copper, inhibitor studies were performed. Using Northern blot analysis, it was shown that antioxidant agent (GSH), calcium chelator (EGTA), plasma membrane calcium channel blocker (La 3+ ) and protein phosphatase inhibitor (cantharidin) inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 62 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…To determine whether VDCC allows extracellular calcium entry, the alga was incubated in 0.5 mL of autoclaved seawater containing 10 mM of the non-specific calcium chelator egtazic acid (EGTA) and 2.5 μM copper; the levels of intracellular calcium were observed. It is important to mention that EGTA has been used as a calcium chelator agent for similar investigations aiming to disclose calcium signaling mechanisms in organisms such as animals, plants and algae ( Johnson & Dufault, 1993 ; Perfus-Barbeoch et al, 2002 ; Hung et al, 2005 ; Gómez et al, 2015 ). To determine whether intracellular calcium is released from the ER, the alga was incubated with 250 nM thapsigargin for 30 min and 2.5 μM copper; intracellular calcium was followed up.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether VDCC allows extracellular calcium entry, the alga was incubated in 0.5 mL of autoclaved seawater containing 10 mM of the non-specific calcium chelator egtazic acid (EGTA) and 2.5 μM copper; the levels of intracellular calcium were observed. It is important to mention that EGTA has been used as a calcium chelator agent for similar investigations aiming to disclose calcium signaling mechanisms in organisms such as animals, plants and algae ( Johnson & Dufault, 1993 ; Perfus-Barbeoch et al, 2002 ; Hung et al, 2005 ; Gómez et al, 2015 ). To determine whether intracellular calcium is released from the ER, the alga was incubated with 250 nM thapsigargin for 30 min and 2.5 μM copper; intracellular calcium was followed up.…”
Section: Methodsmentioning
confidence: 99%
“…Excessive copper specifically activates the MAPK SIMKK, which can activate SIMK and SAMK in Medicago sativa [ 119 ]. Additionally, excess copper activated MAPK2, MAPK3, and MAPK4 in rice roots [ 120 , 121 , 122 ]. ROS burst is one of the earliest events in plants under heavy metal stress, as the ROS act as signaling molecules that regulate the plant’s response to abiotic and biotic stresses [ 123 , 124 , 125 ].…”
Section: Enhanced Plant Resistance To Pathogens and Activation Of Def...mentioning
confidence: 99%
“…The above observations—that is, that CBACs can manage copper-resistant strains and excessive copper can trigger defense-like responses in addition to being toxic to plants [ 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]—indicate that copper may directly trigger plant immunity. Indeed, Liu et al found that a concentration of 10 nM CuSO 4 was sufficient to enhance the resistance of Arabidopsis plants against Pst DC3000 [ 133 ].…”
Section: Eliciting Plant Immunity To Strengthen the Third-tier Barriermentioning
confidence: 99%